2014
DOI: 10.1007/s11130-014-0424-y
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Lupinus albus Gamma Conglutin (Cγ) to n5 STZ Rats Augmented Ins-1 Gene Expression and Pancreatic Insulin Content

Abstract: Several studies support the health-promoting benefits of lupins, particularly lupin proteins. It has been demonstrated that Lupinus albus gamma conglutin (Cγ) protein lowered blood glucose levels; thus, Cγ showed promise as a new anti-diabetic compound for type 2 diabetes (T2D) treatment. The aim of this study was to evaluate the effect of Cγ on Ins-1 gene expression and on pancreatic insulin content in streptozotocin-mediated diabetic rats. Cγ was isolated from Lupinus albus seeds. Its identification was conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 28 publications
4
26
0
1
Order By: Relevance
“…Until now, it has been confirmed that the health promoting properties of lupin seeds are a result of the presence of the protein fraction‐γ‐conglutin, which can be used effectively in the treatment of diabetes . Based on exposure of human hepatocyte cell line (HepG2) to γ‐conglutin, Lovati et al .…”
Section: Introductionmentioning
confidence: 82%
“…Until now, it has been confirmed that the health promoting properties of lupin seeds are a result of the presence of the protein fraction‐γ‐conglutin, which can be used effectively in the treatment of diabetes . Based on exposure of human hepatocyte cell line (HepG2) to γ‐conglutin, Lovati et al .…”
Section: Introductionmentioning
confidence: 82%
“…In addition, Lupinus are more adaptable to regions with low fertility soils and mild or very cold winters compared to soybean cultivation [10]. The seeds of these species represent a functional food ingredient because their proteins are related to the prevention of cardiovascular diseases, and it had been found that their proteins (conglutins) reduce blood glucose in hyperglycemic rats [11,12]. In this way, obtaining protein isolates of Lupinus by isoelectric precipitation is an alternative for the commercial production of food ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that orally administrated c-conglutin reduces glucose levels in hyperglycemic rats (Magni et al, 2004;Lovati et al, 2012). Another study demonstrated that c-conglutin administration improves glucose control and enhances insulin 1 mRNA expression as well as pancreatic insulin content in diabetic rats (Vargas-Guerrero et al, 2014). A recent in vivo study suggested that c-conglutin reduces hepatic glucose production by downregulation of glucose-6-phosphatase expression in insulin resistant and type 2 diabetic rats (Gonzalez-Santiago et al, 2017).…”
Section: Introductionmentioning
confidence: 99%